(untitled) - Masda Surti Simatupang; Ramot Peter; Erni Murniarti (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Batak kinship (in Batak language called partuturon) are fundamental to determine one's position in Batak's culture custom called DalihannaTolu. This study portrayed the kinship systems of DalihannaTolu (three places in the Batak traditions consisting of dongantubu(the relatives with the patriarch surnames or of the identical family names/marga), boru (the relatives from sisters), andhula-hula(the relatives from wife's surnames). The purpose wasto gain a robust and complete comprehending of the Batak kindships of DalihannaTolu in the context of Batak customs/tradition. It contributes to Batak kinship's knowledge of the relationship, the positions, and the proper terms of other people's addresses. Data for this research are the kinship and the standard terms of the address of DalihannaTolu. The procedures of data analysis: first, gathering the data from books, internet, and informationfrom interviewing two Batak natives; next, identifying and classifying the data following the kinship systems of DalihannaTolu; and the last, writing the report of the research. Kinship of DalihannaTolu covers three positions in Batak society representing the three crucial positions in Batak kinship (hula-hula, dongantubu,andboru).